(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We suppose that Ω is a bounded domain in RN (N ≥ 3) with smooth boundary ∂Ω. Consider the quasilinear elliptic equation of p-Kirchhoff type with convection term singular weights